PROSPECTIVE DIRECTIONS OF INTERACTION BETWEEN THE HOLDING AND SERVICING ENTREPRENEURSHIP STRUCTURES OF THE OIL AND GAS COMPLEX - R. Sadykova (Russian Journal of Economics and Law)
The article views new approaches to organization of interaction between entrepreneurship structures of the oil and gas complex.